PENDIDIKAN AKHLAK MENURUT AZ-ZARNUJI DALAM KITAB TA???LIMUL MUTA???ALLIM - Muhammad Wahyudi (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAI Al-Qur'an Al-Ittifaqiah Indralaya, 2020)
With a background in the development of science and technology and the decline in moral education in the community, it is necessary to have a serious study of moral education that is able to provide solutions for education in Indonesia.Ta'lim al-Muta???allim, a book of learning (learning and teaching) especially for students, contains muqaddimah and has 13 fasl (parts). In his muqaddimah, Az-Zarnuji said that in his day, there were so many claimants of knowledge (thalibu al-ilmi) or students who were diligent in learning but were unable to benefit from the knowledge (to practice and spread it). According to him this happens because students have left the requirements that must be fulfilled by every knowledge prosecutor.This journal aims to find out the concepts and values of Moral Education According to Az-ZarnujiIn the Ta'limulMuta'allim Book, the research used is library research, the primary data source is taken from the Ta'limulMuta'allim book, whereas the secondary is taken from other books, jrnal, articles related to research. The technical analysis of the data uses descriptive analytical methods and contec analysis.As for in it there are several educational concepts that are very closely related to education as a transfer of values (values) and not just a transfer of knowledge (intellectual) and skills (skills). Among the concepts of value transfer are as follows: Morals are the main means of education, Teachers, Students, Curriculum, Patterns of Relationships between teachers and students, Methods of moral education.Regarding the teaching methods of moral education, Az-Zarnuji stated three important methods in moral education, including: Methods of moral education with advice, Methods of moral education with mudzakarah (reminding each other), Methods of morality which are more oriented to the concept of compulsory learning with provisions: The purpose and intention of learning, being wara 'at the time of learning, Taking avail (al-Istifadah), Tawakkal in seeking knowledge.Keywords: Moral education, Moral Teaching Method, Ta???lim al-Muta???allim